2022
DOI: 10.1039/d1tc05436h
|View full text |Cite
|
Sign up to set email alerts
|

β-BaGa4Se7: a promising IR nonlinear optical crystal designed by predictable structural rearrangement

Abstract: Rationally designing new inorganic materials with specific functional properties is a fascinating challenge. This is particularly true with the nonlinear optical (NLO) crystals which can expand the spectral ranges of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 63 publications
0
29
0
Order By: Relevance
“…[ 15,28,33,39 ] What's more, the refractive index difference (RID) of DCL‐MgGa 2 Se 4 was investigated by the polarizing microscope method. [ 4d,10,11,40 ] The optical path differences of the DCL‐MgGa 2 Se 4 crystal at 546 nm were 1.48 µm, and the thickness of the crystal was measured to be 31 µm (Figure S8, Supporting Information). According to the Equation () in the Experimental Section, the RID was calculated to be ≈0.048 at 546 nm, which is consistent with the PM behavior.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 15,28,33,39 ] What's more, the refractive index difference (RID) of DCL‐MgGa 2 Se 4 was investigated by the polarizing microscope method. [ 4d,10,11,40 ] The optical path differences of the DCL‐MgGa 2 Se 4 crystal at 546 nm were 1.48 µm, and the thickness of the crystal was measured to be 31 µm (Figure S8, Supporting Information). According to the Equation () in the Experimental Section, the RID was calculated to be ≈0.048 at 546 nm, which is consistent with the PM behavior.…”
Section: Resultsmentioning
confidence: 99%
“…5 pol) with Berek compensator. [ 4d,10,11,40 ] The wavelength of the light source was 546 nm. The RID value is calculated by the following formula: Rbadbreak=||NgNpgoodbreak×Tgoodbreak=normalΔngoodbreak×T\begin{equation} R=\left|{N}_{g}-{N}_{p}\right|\ensuremath{\times{}}T= \Delta n\ensuremath{\times{}}T \end{equation}in which R represents the optical path difference; N g , N p , and Δ n means the refractive index of fast light and slow light, the RID, respectively, and T denotes the thickness of the crystal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, for the tunnel-like Ga-S 3D frameworks, the shape of the tunnels shows abundant diversity. Different from the 6-membered ring tunnel-like 3D framework in BaGa 4 S 7 , BaGa 4 Se 7 and LiGaS 2 , 20,24,25,55 and the 12-membered ring rectangular tunnel-like 3D framework in LiBa 4 Ga 5 Se 12 , 49 the formed 12-membered ring-like tunnels in Na 4 Ga 8 S 14 are rarely reported.…”
Section: Dalton Transactions Papermentioning
confidence: 96%
“…[15][16][17] To enlarge the band gap and enhance the laser-induced damage threshold (LIDT) of chalcogenides, introduction of alkali-and/or alkaline earthmetals has been demonstrated as a feasible method. [18][19][20][21] Recently, a great number of alkali-and/or alkaline earthmetal chalcogenides with wide band gaps have been developed by high temperature solid-state reactions. 22,23 For example, in 2008 Ye et al reported the fabrication of IR NLO material BaGa 4 S 7 , 24 which exhibited a large band gap, high LIDT, wide optically transparent region, and suitable second-order susceptibility coefficients.…”
Section: Introductionmentioning
confidence: 99%